Development of Conjugated Kefiran-Chondroitin Sulphate Cryogels with Enhanced Properties for Biomedical Applications - Hajer Radhouani; Cristiana Gonçalves; F. Raquel Maia; Eduarda P. Oliveira; Rui L. Reis; Joaquim M. Oliveira (MDPI AG, 2023)
Hydrogels based on natural polysaccharides can have unique properties and be tailored for several applications, which may be mainly limited by the fragile structure and weak mechanical properties of this type of system. We successfully prepared cryogels made of newly synthesized kefiran exopolysaccharide-chondroitin sulfate (CS) conjugate via carbodiimide-mediated coupling to overcome these drawbacks. The freeze-thawing procedure of cryogel preparation followed by lyophilization is a promising route to fabricate polymer-based scaffolds with countless and valuable biomedical applications. The novel graft macromolecular compound (kefiran-CS conjugate) was characterized through 1H-NMR and FTIR spectroscopy-which confirmed the structure of the conjugate, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA)-which mirrored good thermal stability (degradation temperature of about 215 °C) and, finally, gel permeation chromatography-size exclusion chromatography (GPC-SEC)-which proved an increased molecular weight due to chemical coupling of kefiran with CS. At the same time, the corresponding cryogels physically crosslinked after the freeze-thawing procedure were investigated by scanning electron microscopy (SEM), Micro-CT, and dynamic rheology. The results revealed a prevalent contribution of elastic/storage component to the viscoelastic behavior of cryogels in swollen state, a micromorphology with micrometer-sized open pores fully interconnected, and high porosity (ca. 90%) observed for freeze-dried cryogels. Furthermore, the metabolic activity and proliferation of human adipose stem cells (hASCs), when cultured onto the developed kefiran-CS cryogel, was maintained at a satisfactory level over 72 h. Based on the results obtained, it can be inferred that the newly freeze-dried kefiran-CS cryogels possess a host of unique properties that render them highly suitable for use in tissue engineering, regenerative medicine, drug delivery, and other biomedical applications where robust mechanical properties and biocompatibility are crucial.